Charge-induced conductance modulation of carbon nanotube field effect transistor memory devices - Chan, Mei Yin (2013)
We effectively tailored the charge trapping and transport behavior of a carbon nanotube field effect transistor memory device using charge interaction with underlying Ge nanoparticles in a HfO2 high-κ dielectric. We also suggest a new route for modulating the Schottky barrier at the nanotube–electrode interface with localized charge trapping in discrete nanoparticles. This modification leads to an effective increase in the read-out conductance ratio of two to three orders magnitude under low voltage operation, associated with a large memory window of ∼5.3 V. Furthermore, we achieved a more controllable and reliable memory effect due to stable charge storage in deep nanoparticle traps, as compared to shallow HfO2 defect states.